The Agriculture–Food Security–Nutrition Nexus: Pathways, Barriers, and Innovations for Sustainable Food Systems - Islam, Saimon; Hossain, Md Mukhtar (AGRIVITA Journal of Agricultural Science, 2026)
Global challenges such as hunger, malnutrition, and environmental degradation highlight the urgent need for a system-based understanding of the relationships among agriculture, food security, and nutrition. This review examines the interconnected nexus of these domains, emphasizing agriculture’s role not only in food production but also in shaping dietary quality and nutritional outcomes. Drawing on interdisciplinary literature, the paper synthesizes evidence on how agricultural intensity influences food availability, access, and utilization, and how nutrition outcomes, in turn, affect agricultural productivity and long-term sustainability. Major constraints, including climate change, weak policy integration, socioeconomic inequalities, and postharvest losses, are analyzed to categorize key barriers to nutrition-sensitive and sustainable food systems. The review further evaluates emerging approaches for nutrition-oriented agricultural development, including agroecological practices, biofortification, climate-smart agriculture, and integrated value chain strategies. Case-based and policy-oriented insights demonstrate the value of cross-sectoral collaboration and systems thinking in addressing complex food system challenges. The findings contribute to ongoing discussions on achieving the Sustainable Development Goals by strengthening linkages among food production, health, and consumption. Overall, the review supports a holistic farm-to-function framework as a foundation for building resilient, equitable, and nutrition-focused food systems while identifying critical research and policy gaps for future work.